When getting there is not enough: a nationwide cross‐sectional study of 998 maternal deaths and 1451 near‐misses in public tertiary hospitals in a low‐income country. (14th May 2015) - Oladapo, OT; Adetoro, OO; Ekele, BA; Chama, C; Etuk, SJ; Aboyeji, AP; Onah, HE; Abasiattai, AM; Adamu, AN; Adegbola, O; Adeniran, AS; Aimakhu, CO; et al.
Abstract : Objective: To investigate the burden and causes of life‐threatening maternal complications and the quality of emergency obstetric care in Nigerian public tertiary hospitals. Design: Nationwide cross‐sectional study. Setting: Forty‐two tertiary hospitals. Population: Women admitted for pregnancy, childbirth and puerperal complications. Methods: All cases of severe maternal outcome (SMO: maternal near‐miss or maternal death) were prospectively identified using the WHO criteria over a 1‐year period. Main outcome measures: Incidence and causes of SMO, health service events, case fatality rate, and mortality index (% of maternal death/SMO). Results: Participating hospitals recorded 91 724 live births and 5910 stillbirths. A total of 2449 women had an SMO, including 1451 near‐misses and 998 maternal deaths (2.7, 1.6 and 1.1% of live births, respectively). The majority (91.8%) of SMO cases were admitted in critical condition. Leading causes of SMO were pre‐eclampsia/eclampsia (23.4%) and postpartum haemorrhage (14.4%). The overall mortality index for life‐threatening conditions was 40.8%. For all SMOs, the median time between diagnosis and critical intervention was 60 minutes (IQR: 21–215 minutes) but in 21.9% of cases, it was over 4 hours. Late presentation (35.3%), lack of health insurance (17.5%) and non‐availability of blood/blood products (12.7%) were the most frequent problems associated with deficiencies in care. Conclusions: Improving the chances of maternal survival would not only require timely application of life‐saving interventions but also their safe, efficient and equitable use. Maternal mortality reduction strategies in Nigeria should address the deficiencies identified in tertiary hospital care and prioritise the prevention of severe complications at lower levels of care. Tweetable abstract: Of 998 maternal deaths and 1451 near‐misses reported in a network of 42 Nigerian tertiary hospitals in 1 year. Tweetable abstract: Of 998 maternal deaths and 1451 near‐misses reported in a network of 42 Nigerian tertiary hospitals in 1 year.